Diagnosing fast ion redistribution due to sawtooth instabilities using fast ion deuterium-α spectroscopy in the mega amp spherical tokamak. (21st October 2020) - Jackson, A.R.; Jacobsen, A.S.; McClements, K.G.; Michael, C.A.; Cecconello, M.
Abstract: A comparison between fast ion measurements and sawtooth models in the Mega Amp Spherical Tokamak (MAST) is extended to include fast ion deuterium-alpha (FIDA) data. It is concluded that FIDA data cannot be used to distinguish between three alternative models used in the plasma transport/fast particle code TRANSP/NUBEAM to simulate fast ion redistribution during sawteeth. For FIDA lines-of-sight that probe the sawtoothing region, at each sawtooth crash there is an overall drop in the emission of up to 60%. Data from passive FIDA lines-of-sight ( i.e. with emission resulting from neutralisation by thermal neutrals in the plasma periphery rather than beam neutrals) show a sudden increase in the emission following sawtooth crashes. The subsequent decay in the emission in these passive channels indicates that redistributed passing fast ions are rapidly lost from the edge region, probably as a result of charge-exchange reactions with edge neutrals.